Tolerance and Withdrawal From Prolonged Opioid Use in Critically Ill Children - Anand, Kanwaljeet J. S. (2010)
OBJECTIVE: After prolonged opioid exposure, children develop opioid-induced hyperalgesia, tolerance, and withdrawal. Strategies for prevention and management should be based on the mechanisms of opioid tolerance and withdrawal. PATIENTS AND METHODS: Relevant manuscripts published in the English language were searched in Medline by using search terms “opioid,” “opiate,” “sedation,” “analgesia,” “child,” “infant-newborn,” “tolerance,” “dependency,” “withdrawal,” “analgesic,” “receptor,” and “individual opioid drugs.” Clinical and preclinical studies were reviewed for data synthesis. RESULTS: Mechanisms of opioid-induced hyperalgesia and tolerance suggest important drug- and patient-related risk factors that lead to tolerance and withdrawal. Opioid tolerance occurs earlier in the younger age groups, develops commonly during critical illness, and results more frequently from prolonged intravenous infusions of short-acting opioids. Treatment options include slowly tapering opioid doses, switching to longer-acting opioids, or specifically treating the symptoms of opioid withdrawal. Novel therapies may also include blocking the mechanisms of opioid tolerance, which would enhance the safety and effectiveness of opioid analgesia. CONCLUSIONS: Opioid tolerance and withdrawal occur frequently in critically ill children. Novel insights into opioid receptor physiology and cellular biochemical changes will inform scientific approaches for the use of opioid analgesia and the prevention of opioid tolerance and withdrawal.